Design and analysis of sequence generator module using eulerian path algorithm for DNA fragment assembly: article / Mustaqim Mohd Subri - Mohd Subri, Mustaqim (2013)
This project is to design and analyze of sequence generator module using Eulerian Path Algorithm for DNA fragment assembly. Mostly, “overlap – layout - consensus” method is used to assemble DNA, but a new system need to be introduced to overcome problems in assembling long DNA sequence in this method. Euler Path Algorithm is used since it has better assembling ability especially in assembling long sequence. The objective of this project is to design the DNA sequence generator modules using the Eulerian Path Algorithm. This project is designed based on speed optimization. DNA fragment assembly is a process reassembling fragment of DNA like a puzzle into several other sequence. DNA fragment assembly consists of two process, assembling and alignment. For FPGA design, synthesis and simulation is done using the Xilinx Vivado software to obtain the RTL schematic as well as the waveform of the module. In ASIC design, Synopsys tools is used for analysis the project. Tools used are VCS for re verifying the design for further process in ASIC design, DC for resynthesize and remodeling the design with constraints and lastly static timing analysis using PT for advanced static timing analysis. The average area for normal-compile using DC is 413,309.1um2 while for ultra-compile is 83,096.06um2. The average dynamic power and leakage power for normal compile is 159.0887uW and 1.8045mW, while for “compile ultra” is 99.09uW and 263.54uW. From comparison with timing analysis in DC and STA in PT, this system can be run on minimum 600ns period. Based on the result obtained, this project has been successfully designed and simulated on FPGA and ASIC design flow.